Pharmacological targeting of the transcription factor SOX18 delays breast cancer in mice - Jeroen Overman; Frank Fontaine; Mehdi Moustaqil; Deepak Mittal; Emma Sierecki; Natalia Sacilotto; Johannes Zuegg; Avril AB Robertson; Kelly Holmes; Angela A Salim; Sreeman Mamidyala; Mark S Butler; et al. (eLife, 2017)
Pharmacological targeting of transcription factors holds great promise for the development of new therapeutics, but strategies based on blockade of DNA binding, nuclear shuttling, or individual protein partner recruitment have yielded limited success to date. Transcription factors typically engage in complex interaction networks, likely masking the effects of specifically inhibiting single protein-protein interactions. Here, we used a combination of genomic, proteomic and biophysical methods to discover a suite of protein-protein interactions involving the SOX18 transcription factor, a known regulator of vascular development and disease. We describe a small-molecule that is able to disrupt a discrete subset of SOX18-dependent interactions. This compound selectively suppressed SOX18 transcriptional outputs in vitro and interfered with vascular development in zebrafish larvae. In a mouse pre-clinical model of breast cancer, treatment with this inhibitor significantly improved survival by reducing tumour vascular density and metastatic spread. Our studies validate an interactome-based molecular strategy to interfere with transcription factor activity, for the development of novel disease therapeutics.